Structural Studies of Transition Metal Complexes of 2-Furoin Oxime - Singh, S.G.; Mehta, B.H. (Asian Journal of Chemistry, 2010)
The synthesized palladium, ruthenium and rhodium complexes of 2-furoin oxime contained the metal:ligand stoichiometry 1:2 for palladium complex and 1:3 for ruthenium and rhodium complexes. The ligand and its metal complexes were characterized for various analytical parameters and spectral features. The structures of these complexes are also proposed.